PENGARUH MOTIVASI TERHADAP PENINGKATAN KINERJA KARYAWAN PT. BANK CENTRAL ASIA CABANG GOLDEN TRADE MEDAN - YULIANA .; JEFFRY .; AZWIN AKBAR; WENY .; MICHAEL JACKSON (JURNAL ILMIAH SIMANTEK, 2019)
Human resources are important assets that have the ability to develop as a determinant of the company's success in thelong term. Having a proven human resource capability, skill, loyal to the company, eager in achieving the goal of thecompany will keep the company able to compete in the era of globalization. Motivation to the employees must becontinuously done, this is intended to be the skills, knowledge, attitude, loyalty, morale and commitment to the companyincreases so that each job will be more easily completed on time and on target so as to improve the performance ofemployees impact is the productivity and profitability of the company will increase. The purpose of the research is to knowthe motivation given by the company impact on the performance of employees of PT. Bank Central Asia Branch GoldenTrade Centre Medan. The research method used is an associative quantitative method. The number of samples as many as30 employees with sampling techniques is a saturated sample. The results of the study stated that strong motivation on theperformance of employees of PT. Bank Central Asia Golden Trade Centre Branch of Medan can be seen in the results ofanalysis of coefficient of determination (R2) of 29.9%. So it can be concluded that the performance of employees ofPT. Bank Central Asia Medan Golden Trade Centre Branch is 29.9% influenced by motivation, while the remaining 70.1% isinfluenced by other factors that are not researched in this study, so it is recommended that the next researcher to be able toresearch using other factors besides the motivation factor to know their impact on employee performance.